Factors affecting bond strength between acrylic dental elements and thermoplastic nylon bases: a systematic literature review - Imas Maesaroh; Marzia Magdalena Tetelepta; Heldayani Heldayani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Objective: To determine the factors influencing bond strength between acrylic tooth elements and thermoplastic nylon denture bases. Methods: A systematic literature review was conducted using the PRISMA framework. An electronic search was conducted in Semantic Scholar, Google Scholar, Crossref, and Scopus for studies published between 2015 and 2025. Keywords included “thermoplastic nylon,” “polyamide denture base,” “acrylic denture,” and “bond strength.” In vitro experimental studies examining bond strength at the tooth-base interface were included. After screening 185 identified records, 18 studies met eligibility criteria and were included in the qualitative synthesis. Results: Four primary factors influence bond strength: (1) the role of surface treatment in enhancing bond strength, (2) material composition and brand variation, (3) processing and repair techniques, and (4) denture design. Mechanical surface treatments, specifically, aluminum oxide sandblasting and macro-retentive preparation, consistently improved shear and tensile bond strength. Significant variability was observed between nylon brands, with some materials demonstrating superior bond performance. Reinjection techniques and microwave polymerization improved interfacial integrity compared to manual heating or conventional repair methods. Conversely, some modified materials, such as nanoparticle incorporation, negatively impacted mechanical stability. Conclusion: The bond strength between acrylic dentures and thermoplastic nylon bases is largely governed by mechanical retention rather than chemical adhesion. Optimal bonding requires integrated consideration of material selection, standardized surface treatments, and controlled maintenance techniques. Further standardized and long-term studies are needed to establish evidence-based clinical guidelines.